Penggunaan Jamu pada Kasus Covid-19 Gejala Ringan di Pelayanan Kesehatan Tradisional di Jakarta (Studi Pendahuluan): The Utilization of Jamu in Treating Mild Covid-19 Symptoms at a Griya Sehat in Jakarta (Preliminary Studies) - Widowati, Lucie; Delima, Delima; Japaris, Wiily (Universitas Tidar, 2023)
Background: In the COVID-19 pandemic situation, herbal medicine is quite widely used by people. Objective: to assess the description of the handling of mild cases of COVID-19 clients using herbal ingredients, which was carried out at a Traditional Health Care Center in Jakarta. Method: Descriptive research with retrospective case study design on mild COVID-19 cases using or being treated with traditional Indonesian herbal medicine, using secondary data from medical records from 30 COVID-19 clients who had COVID-19 status based on PCR examination. Results: There were 7 types of herbs given either as a single herb or a combination of them. Most of the ingredients used were sambiloto capsules and Jamu B concoction. After drinking the potions, 21 clients were symptom free on day 14, 2 clients were symptom free on days 5 and 7 and were noted to have a habit of drinking jamu for physical fitness. Cumulatively, all clients were symptom free on day 23 with stable condition in 8 clients (26.7%) and 22 clients (73.3%) stated that they were getting lighter. The most cases of transmission of COVID-19 to people around them were 5 clients who infected 5 people. All infected people have mild/asymptomatic COVID-19. Conclusion: Herbal medicine has the potential to be used for COVID-19 clients with mild/asymptomatic complaints, and the habit of drinking herbal concoctions for fitness can shorten the day of symptom relief compared to those who do not drink herbal medicine before getting sick.